Ethnic-Racial Identity as a Source of Resilience and Resistance in the Context of Racism and Xenophobia. Issue 3 (September 2022) - Rivas-Drake, Deborah; Pinetta, Bernardette J.; Juang, Linda P.; Agi, Abunya
How youth come to understand their social identities and their relation to others' identities can have important implications for the future of our society. In this article, we focus on how ethnic-racial identities (ERI) can serve to promote (or hinder) collective well-being. We first describe the nature of change in ethnic-racial identities over the course of childhood and adolescence. We then delineate three pathways by which youths' ERI can be a mechanism for productive intergroup relations and thereby collective well-being as a: (a) basis for understanding differences and finding commonalities across groups; (b) promotive and protective resource for marginalized youth; and (c) springboard for recognizing and disrupting marginalization. This article concludes with how youths' ERI can be nurtured into a source of resilience and resistance in the face of racism and xenophobia. Moreover, we urge researchers to consider the role ERI plays in guiding youth to challenge and resist marginalization.